2002
DOI: 10.1016/s1010-7940(02)00073-8
|View full text |Cite
|
Sign up to set email alerts
|

Stage I palliation for hypoplastic left heart syndrome in low birth weight neonates: can we justify it?1

Abstract: LBW newborns with HLHS and physiologic variants have an increased early surgical risk but have acceptable intermediate survival rates for subsequent palliation including Fontan. LBW and prematurity should not be contraindications to early surgical palliation.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

4
38
1

Year Published

2002
2002
2023
2023

Publication Types

Select...
3
3
1

Relationship

0
7

Authors

Journals

citations
Cited by 57 publications
(43 citation statements)
references
References 19 publications
4
38
1
Order By: Relevance
“…The association between genetic syndromes and extracardiac malformations and mortality after the Norwood operation is well established in older studies and, similar to our current series, continues to be evident in more recent studies including the SVR trial [1,3,5,9,13]. A recent study showed that genetic and extracardiac anomalies were associated with increased operative death and hospital stay in neonates who underwent the Norwood operation as recorded in the Society of Thoracic Surgeons (STS) database, in addition to increased early hazard of death and decreased 10-year survival in neonates who underwent the Norwood operation as recorded in the Congenital Hearts Surgeons Society database [13]. We recently analyzed the effect of genetic and extracardiac anomalies on the outcomes of cardiac operations on neonates at our institution and identified that those anomalies were associated with increased resource utilization, ventilation duration, intensive care and hospital stays, and hospital mortality.…”
Section: Commentsupporting
confidence: 84%
“…The association between genetic syndromes and extracardiac malformations and mortality after the Norwood operation is well established in older studies and, similar to our current series, continues to be evident in more recent studies including the SVR trial [1,3,5,9,13]. A recent study showed that genetic and extracardiac anomalies were associated with increased operative death and hospital stay in neonates who underwent the Norwood operation as recorded in the Society of Thoracic Surgeons (STS) database, in addition to increased early hazard of death and decreased 10-year survival in neonates who underwent the Norwood operation as recorded in the Congenital Hearts Surgeons Society database [13]. We recently analyzed the effect of genetic and extracardiac anomalies on the outcomes of cardiac operations on neonates at our institution and identified that those anomalies were associated with increased resource utilization, ventilation duration, intensive care and hospital stays, and hospital mortality.…”
Section: Commentsupporting
confidence: 84%
“…Low weight has persistently been demonstrated as a risk factor for mortality after the Norwood operation, including in recent series from experienced institutions [11,12,14]. Similarly, low weight has been associated with increased mortality risk after BTS due to shunt occlusion related to the small sized shunts or systemic steal due to excessive pulmonary blood flow that is likely more common in smaller babies [16,17].…”
Section: Commentmentioning
confidence: 97%
“…In addition to early death, low weight at time of firststage surgery was suggested to have an adverse effect on late survival [3,11,12]. Gelehrter and colleagues [11] reviewed outcomes of 47 neonates with HLHS patients who were 2.5 kg or less at time of Norwood palliation.…”
Section: Commentmentioning
confidence: 99%
See 2 more Smart Citations